2021
DOI: 10.1021/acsami.1c06225
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Nanotransfer Printing Based on Water Bridge Formation in Hyaluronic Acid and Its Application to Smart Contact Lenses

Abstract: Many conventional micropatterning and nanopatterning techniques employ toxic chemicals, rendering them nonbiocompatible and unsuited for biodevice production. Herein the formation of water bridges on the surface of hyaluronic acid (HA) films is exploited to develop a transfer-based nanopatterning method applicable to diverse structures and materials. The HA film surface, made deformable via water bridge generation, is brought into contact with a functional material and subjected to thermal treatment, which res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…In particular, poly­(carboxylic acid)­s are useful in many fields because of their distinct intrinsic properties, such as hydrophilicity, pH responsibility, and hydrogen-bonding capability. For example, as one of the most widely used polysaccharides, alginic acid derived from brown seaweeds has a broad range of potential applications in food, medicines, environmental protection, and packaging. , In addition, because of its superior hydration and biocompatibility, hyaluronic acid found in the human skin is used in food, medical, pharmaceutical, and cosmetic industries. , As a synthetic analogue to these natural poly­(carboxylic acid)­s, poly­(acrylic acid)­s and poly­(methacrylic acid)­s are also widely employed in adhesives, dispersants, absorbents, and drug delivery systems. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, poly­(carboxylic acid)­s are useful in many fields because of their distinct intrinsic properties, such as hydrophilicity, pH responsibility, and hydrogen-bonding capability. For example, as one of the most widely used polysaccharides, alginic acid derived from brown seaweeds has a broad range of potential applications in food, medicines, environmental protection, and packaging. , In addition, because of its superior hydration and biocompatibility, hyaluronic acid found in the human skin is used in food, medical, pharmaceutical, and cosmetic industries. , As a synthetic analogue to these natural poly­(carboxylic acid)­s, poly­(acrylic acid)­s and poly­(methacrylic acid)­s are also widely employed in adhesives, dispersants, absorbents, and drug delivery systems. , …”
Section: Introductionmentioning
confidence: 99%
“…21,28 In addition, because of its superior hydration and biocompatibility, hyaluronic acid found in the human skin is used in food, medical, pharmaceutical, and cosmetic industries. 22,29 As a synthetic analogue to these natural poly(carboxylic acid)s, poly(acrylic acid)s and poly-(methacrylic acid)s are also widely employed in adhesives, 30 dispersants, 31 absorbents, 32 and drug delivery systems. 33,34 Despite the significant progress made in the synthesis of poly(carboxylic acid)s, only a few studies reported the synthesis of polyethers possessing carboxylic acid function- alities.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Therefore, PDMS can be combined with other constituent materials to impart elastomeric functions. These elastomers act as substrates or carriers, interconnecting the interface between the soft human body and high modulus components (for example, metal and electronic devices). ,, In turn, HA is a hydrophilic linear polysaccharide containing d -glucuronic acid, which combines N-acetyl- d -glucosamine as a disaccharide decomposing unit and has excellent biocompatibility and biodegradability, making it a highly stable material (Figure a,ii). Figure a (1–2) presents the mechanism of generation of this composite film based on the incompatibility of the binary polymer mixtures.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, to achieve asymmetric adhesion with soft properties by dynamically changing the elasticity of the material, in this study, we propose the formation of asymmetric adhesion based on phase separation by physically mixing a hydrophilic HA polymer solution and a hydrophobic polydimethylsiloxane (PDMS) solution, which is expected to achieve the sensitive characteristics of adhesive/nonadhesive properties depending on the degree of cross-linking. HA is a natural nonirritating polysaccharide hydrophilic polymer that is used as an additive and is a highly stable material that can be applied in various fields, such as cosmetics, drug delivery, micro/nanopatterning-based wearables, and implantable devices. Therefore, the present strategy is expected to produce a soft and flexible asymmetric adhesive film for easy application in wearable and attachable biomedical devices, with controllable surface properties related to adhesion, flexibility, transmittance, and thickness.…”
mentioning
confidence: 99%
“…Research pertaining to precisely designed nanophotonic devices on various substrates has recently received considerable attention driven by the growing demand for diverse mechanical and optical properties in optical elements, such as those used in augmented reality (AR) and virtual reality (VR) systems, sensors, lenses, and flexible and stretchable displays . In this regard, nanotransfer printing (nTP) has been extensively studied in industry and academia as a fabrication technique because of its ability to repeatedly produce large-area nanostructures with high efficiency. The basic mechanism of nTP relies on the adhesion force between the mold and material ( F 1 ) being weaker than the adhesion force between the material and substrate ( F 2 ) .…”
Section: Introductionmentioning
confidence: 99%